Theoretical research flow total amount of heat through the walls of particular channel - Kalassov, N.B.; Manatbayev, R.K. (Recent Contributions to Physics, 2013)
The Republic of Kazakhstan in terms of geography is in a wind zone of the northern hemisphere, and in large parts of Kazakhstan, fairly strong air currents, mainly the north-east, south-west. In some regions of Kazakhstan annual average wind speed is greater than 6 m / s, which makes the area attractive for wind power development. In times of greatest need in heat and power turbine can be damaged due to wet snow drifts, followed by a sharp decrease in air temperature and the formation of heavy ice on them. One possible way to protect the outer surface of the operating wind turbines on wet snow is heated by warm air flowing through the internal channels apparatus. Thermal protection is a more radical way. This paper discusses the method of calculation of the heat flow of air through the wall of the machine. Using this technique, the total costs were determined amount of heat on the walls of a particular channel.